Psychological well-being as an indicator of self-actualization of a person (Actual Problems of Psychology in Educational Institutions, 2019)
The article analyzes the theoretical principles of the problem ofself-actualization and psychological well-being of the individual. The maincharacteristics of these phenomena are described and the features of theirconnection are investigated. The main components of self-actualization areconsidered, as tendencies to realization of internal potential and development ofown abilities. The structure and features of the formation of psychologicalwell-being of a person are determined. It is revealed that psychologicalwell-being, reflecting the internal state of the individual, is a criterion for howan individual is satisfied with himself and his life and serves as an indicator of aperson's orientation towards self-actualization.
Keywords: self-actualization; well-being; psychological well-being; implementation; development; satisfaction